Journal of a third voyage for the discovery of a north-west passage from the Atlantic to the Pacific [electronic resource] : performed in the years 1824-25, in His Majesty's ships, Hecla and Fury, under the orders of Captain William E. Parry, R.N., F.R.S., and commander of the expedition. - Parry, William Edward, Sir, 1790-1855. (London : J. Murray, 1826)
Tables. Errata--p. [152]. "Published by authority of the Lords Commissioners of the Admiralty." "Illustrated by plates and charts." Electronic reproduction. Mode of access: Internet. 44